Globalization and top income shares - MA, Lin (Institutional Knowledge at Singapore Management University, 2020)
This paper documents empirically that access to global markets is associated with a higher executive-to-worker pay ratio within the firm. It then uses China's 2001 accession to the World Trade Organization as a trade shock to show that firms that exported to China prior to 2001 subsequently exported more, grew larger, and grew more unequal in terms of executive-to-worker pay. To evaluate analytically and quantitatively the impacts of globalization on top income inequality, this paper builds a model with heterogeneous firms, occupational choice, and executive compensation. In the model, executive compensation grows with the size of the firm, while the wage paid to ordinary workers is determined in a country-wide labor market. As a result, the extra profits earned in the foreign markets benefit the executives more than the average workers. We calibrate the model to the U.S. economy and match the income distribution closely in the data. Counterfactual exercises suggest that trade and FDI liberalizations can explain around 44% of the surge in top 0.1% income shares in the data between 1988 and 2008.